Improving the Quality of Teaching and Learning Activities using Information Technology at Orange Islamic School Palembang, South Sumatra: Peningktan Kualitas Kegiatan Belajar Mengajar menggunakan Teknologi Informasi di Orange Islamic School Palembang Sumatera Selatan - Zulhipni Reno Saputra Elsi; Meli Astriani; Randy Hidayat; Moehammad Irfansyah; David Agustianto Rapel (Universitas Lancang Kuning, 2024)
Education is an important factor in community development. In the current digital era, the use of information technology in teaching and learning activities is the key to increasing the effectiveness and efficiency of the learning process. In this PkM, we aim to improve the quality of teaching and learning activities using information technology at Orange Islamic School in Palembang, South Sumatra. Our PkM implementation methods include introducing and applying technological information in the learning process, training teachers to use technological information, and involving parents in education. We also collect data to disseminate the impact of using information technology in teaching and learning activities. The results of this PkM show that the use of information technology at Orange Islamic School has succeeded in improving the quality of teaching and learning activities. Teachers can deliver learning material in a more interesting and interactive way, thereby increasing student participation and understanding. The use of information technology in teaching and learning activities at Orange Islamic School has made a significant contribution to improving the quality of education.